Innovations in teacher education : a social constructivist approach - Beck, Clive (SUNY series in teacher preparation and development., 2006)
"This book offers a comprehensive, "social constructivist" approach to preservice education. Written in a clear, accessible style, it presents key principles of teacher education and concrete examples from eight successful programs in Australia, Canada, and the United States. It extends constructivism beyond Piaget and Vygotsky to more recent theorists such as Barthes and Derrida, indicating how such an approach can lead to engaging, effective education. Clive Beck and Clare Kosnik advocate an approach to teacher education that is highly original, linking integration, community components, and inquiry to a degree not commonly found in preservice programs, and they show in detail how to implement these elements."--Jacket